1996
DOI: 10.1002/(sici)1097-4628(19961121)62:8<1133::aid-app1>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of surface-modifying macromolecules for use in segmented polyurethanes

Abstract: SYNOPSISPolyurethanes are one of the most important classes of thermoplastic elastomers and have been widely used in medical-device manufacturing as well as in other applications. However, their function can be limited, particularly under environmental conditions that render them susceptible to hydrolysis. Using polymeric additives that are hydrolytically stable may be one approach to modifying the surface of polyurethanes for the purpose of improving their hydrolytic resistance without compromising their stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
110
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(116 citation statements)
references
References 1 publication
5
110
0
1
Order By: Relevance
“…2 Lysine diisocyanate was distilled under vacuum stored in sealed ampoules and used within three months. The fluoroalcohol was distilled as described elsewhere [6] and degassed under vacuum at 40 1C prior to synthesis. A reactant ratio of 2:1:2 (diisocyanate/PTMO diol/fluoroalcohol) was used, and the reaction was catalyzed using dibutyl tin dilaurate (DBTDL).…”
Section: Bfsm Precursor Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…2 Lysine diisocyanate was distilled under vacuum stored in sealed ampoules and used within three months. The fluoroalcohol was distilled as described elsewhere [6] and degassed under vacuum at 40 1C prior to synthesis. A reactant ratio of 2:1:2 (diisocyanate/PTMO diol/fluoroalcohol) was used, and the reaction was catalyzed using dibutyl tin dilaurate (DBTDL).…”
Section: Bfsm Precursor Synthesismentioning
confidence: 99%
“…To determine the effect of fluorine in the absence of the bioactive peptide on cellular interactions with PCNU surfaces, a nonbioactive SMM, synthesized with HDI, PTMO, and fluoroalcohol in a 2:1:2 ratio, was used in this study. This material will be referred to as an SMM, and was synthesized in-house using previously reported techniques [6].…”
Section: Base Polymer Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…These materials combine some of the virtues of polyurethane and fluorinated acrylate/acrylate polymer, such as high thermal stability, good chemical resistance, low water absorptivity (water resistance), attractive surface properties, excellent flexibility, good wearability and high weatherability [12,[36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Santerre et al [20,21] mixed fluorine-containing polyurethanes, used as surface-modifying macromolecules, with base polyurethanes to alter the surface chemistry of the base polyurethanes, thereby altering their biostability and/or biocompatibility. Tonelli et al [16] showed that fluorinated polyurethanes with different fluorine content are not thrombogenic and not cytotoxic.…”
Section: Introductionmentioning
confidence: 99%